The process of drafting and revising guidelines for NTFP certification - Shanley, P.; Laird, S.A. (Routledge, 2002)
The process of creating the NTFP guidelines involved numerous experts and collaborators across the globe, with a particular emphasis on Latin America. The guidelines were drafted between 1997 and 1998, with input from the NTFP certification advisory committee, certification experts and other forestry and NTFP specialists. Field-testing took place in three countries: Mexico (chicle), Bolivia (Brazil nut and palm heart), during the first half of 1998.